ADAPTATION OF THE STATE UNIVERSITY-LEGAL ENTITY"™S EMPLOYEES ON WORK PATTERN CHANGES DURING COVID-19 PANDEMIC - Heryanto, Weko; Sukmawati, Anggraini; Sjafri, Aida Vitayala (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
The COVID-19 pandemic phenomenon is causing increased stimulus to digital acceleration, and organizational work patterns change, thus creating a new work way for X University employees. Human resources management should keep on striving to retain employees as an essential asset. The purpose of this research is to analyze supporting factors and strategize to improve the adaptability of the education supporting staff of X University in changing situations as a result of the COVID-19 pandemic. The number of respondents who filled in the online questionnaire and were selected by using a purposive sampling method was 297 respondents. The data analysis tool used in this study is Structural Equation Modeling-Partial Least Square (SEM-PLS). The research found that engaging leadership, human resources management practice and job demands had no direct effect on work engagement. Job resources and personal resources had a direct effect on work engagement. Engaging leadership, human resources management practice, job demands, and job resources had no direct effect on performance. Personal resources and work engagement had a direct effect on performance. Work engagement was able to become a mediator for job resources and personal resources towards performance.